Institutional Environment for the "Green" Economy Development in Khanty-Mansi Autonomous Okrug–Yugra - ISLAMUTDINOV, V. F.; LEBEDEVA, I. D.; BURUNDUKOVA, E. M.; KOROSTELEVA, V. V.; RAZDROKOV, E. N. (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021DO - 10.14505/jemt.12.7(55).13, 2021)
The paper studies the prerequisites for the "green" economy development in Khanty-Mansi Autonomous Okrug–Yugra ( KHMAO-Yugra ) . The development degree of the institutional environment of the "green" economy in Russia is compared to the CIS, European and Asian states. Based on statistical data, the scale of the prevalence of "green" economy elements in Yugra is estimated. The composition and the state of the institutional environment of the "green" economy in Russia and in Yugra are described. The features of the institutional vacuum and institutional traps of the "green" economy development in Yugra are revealed. Proposals on the institutional environment change at the regional and federal levels for the "green" economy development stimulation are given .